1999
DOI: 10.1152/ajpregu.1999.277.1.r112
|View full text |Cite
|
Sign up to set email alerts
|

Renal medullary interstitial infusion of norepinephrine in anesthetized rabbits: methodological considerations

Abstract: We tested methods for delivery of drugs to the renal medulla of anesthetized rabbits. Outer medullary infusion (OMI) of norepinephrine (300 ng ⋅ kg−1 ⋅ min−1), using acutely or chronically positioned catheters, reduced both cortical (CBF; 15%) and medullary perfusion (MBF; 23–31%). Inner medullary infusion (IMI) did not affect renal hemodynamics, whereas intravenous infusion reduced CBF (15%) without changes in MBF. During OMI of [3H]norepinephrine, much of the radiolabel (∼40% with chronically positioned cath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 16 publications
5
23
0
Order By: Relevance
“…Because these vasoconstrictors can be accumulated in ischemic kidney and stimulate medullary NO production, it is possible that decreases in medullary cGMP levels during reductions in RBF are partially buffered. Although other possibilities cannot be ruled out, our results support the hypothesis based on the results of previous studies (5,7,11,29,38,40) that the lesser responses of medullary cGMP to reductions in RBF may play an important role in protecting the renal medulla from ischemic injury.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Because these vasoconstrictors can be accumulated in ischemic kidney and stimulate medullary NO production, it is possible that decreases in medullary cGMP levels during reductions in RBF are partially buffered. Although other possibilities cannot be ruled out, our results support the hypothesis based on the results of previous studies (5,7,11,29,38,40) that the lesser responses of medullary cGMP to reductions in RBF may play an important role in protecting the renal medulla from ischemic injury.…”
Section: Discussionsupporting
confidence: 91%
“…Another possibility is that acute changes in blood flow differentially influenced NO-mediated cGMP production in the cortex and medulla. Recent studies have suggested norepinephrine (5,11,38), angiotensin II (40), and arginine vasopressin (7,29) receptor-mediated activation of NOS predominantly in the renal medulla. Because these vasoconstrictors can be accumulated in ischemic kidney and stimulate medullary NO production, it is possible that decreases in medullary cGMP levels during reductions in RBF are partially buffered.…”
Section: Discussionmentioning
confidence: 99%
“…The left kidney was exposed via a flank incision and placed in a cup secured to the operating table. Catheters was placed in the left ureter and left renal vein (6). The kidney was denervated, and a transit-time ultrasound flow probe (type 2SB; Transonic Systems, Ithaca, NY) was placed around the renal artery for measurement of RBF.…”
Section: Animalsmentioning
confidence: 99%
“…In 14 rabbits, medullary infusion catheters were acutely positioned laterally, 10 mm either side of the laser-Doppler flow probe, and advanced so that their tips lay 8.5 mm below the cortical surface (at the junction of the outer and inner stripes of the outer medulla). 5 The extracorporeal circuit was then established, and RAP was set at Ϸ65 …”
Section: Extracorporeal Circuitmentioning
confidence: 99%
“…To this end, we made use of our recent observation that medullary interstitial infusion of norepinephrine (NE) reduces MBF twice as much as CBF, whereas intravenous NE reduces only CBF. 5 Therefore, we compared the effects of medullary interstitial infusion and intravenous infusion of NE on antihypertensive responses to increased RAP. Thus, using this experimental design, we could control for the effects of NE exerted outside the renal medulla in a way that was not possible in our previous experiment with the V 1 -agonist.…”
mentioning
confidence: 99%